Whole Genome Resequencing of 20 Accessions of Rice Landraces Reveals Javanica Genomic Structure Variation and Allelic Genotypes of a Grain Weight Gene TGW2 - Long, Weixiong; Luo, Lihua; Luo, Laiyang; Xu, Weibiao; Li, Yonghui; Cai, Yaohui; Xie, Hongwei (Frontiers in plant science, 2022)
The landraces preserved by indigenous worldwide exhibited larger variation in the phenotypes and adaption to different environments, which suggests that they comprise rich resources and can be served as a gene pool for rice improvement. Despite extensive studies on cultivated rice, the variations and relationships between landraces and modern cultivated rice remain unclear. In this study, a total of 20 varieties that include 10 Oryza javanica collected from different countries worldwide and 10 Oryza indica from China were genotyped and yielded a sum of 99.9-Gb resequencing raw data. With the genomic sequence of the japonica cultivar Nipponbare as a reference, the following genetic features of single-nucleotide polymorphism (SNP) ranged from 861,177 to 1,044,617, insertion–deletion polymorphisms (InDels) ranged from 164,018 to 211,135, and structural variation (SV) ranged from 3,313 to 4,959 were identified in Oryza javanica. Variation between the two subspecies was also determined that 584,104 SNPs, 75,351 InDels, 104,606 SNPs, and 19,872 InDels specific to Oryza indica and Oryza javanica, respectively. Furthermore, Gene Ontology (GO) and KEGG of Oryza javanica-specific SNP-related genes revealed that they participated in DNA metabolic process, DNA replication, and DNA integration. The sequence variation and candidate grain shape-related gene TGW2 were identified through Fst and sweep selective analysis. Hap4 of TGW2 is performed better than others. The whole genome sequence data and genetic variation information illustrated in this study will serve as an important gene pool for molecular breeding and facilitate genetic analysis of Oryza javanica varieties.